Spanish Relief Funds (circular) - Elger, William
029-0029-001 Scottish Trades Union Congress General Council. 33 Elmbank Crescent, GLASGOW. William Elger, J.P. Secretary. PHONE CENTRAL 3179 FOR INFORMATION January 24th. 1938. To the Secretary of the Union or Trades Council named in the address. Ref. C.51. (1937-38). Dear Sir, SPANISH RELIEF FUNDS The General Council have been informed that the National Joint Committee for Spanish Relief has suggested the setting up of area joint committees in Scotland. It is proposed that all monies collected be passed to the National Joint Committee, "who will distribute it to the existing organisations at present doing relief work, with special preference to the needs of existing Scottish organisations. The General Council desire to remind all sections of the Trade Union Movement that it is undesirable to diffuse their energy in the collection of monies for Spanish relief or to encourage any overlapping in the methods by which such monies are administered. All contributions collected by the trade unions should therefore be forwarded to the National Council of Labour whose contact with the International Solidarity Fund and the Milk for Spain Fund should be made as effective as possible. In the administration of the former substantial regard has already been had to the needs of Scottish organisations, and with regard to the latter the General Council have recently urged the necessity for a large volume of support from Scotland. Your Union or Council is therefore requested specially to advise its branches in Scotland to concentrate their efforts upon the Funds promoted and administered by the National Council of Labour. The adoption of such a course will make unnecessary and undesirable any association of trade union branches and Trades Councils with area committees of the National Joint Council for Spanish Relief. Trade union branches and Trades Councils should not be represented at meetings called by this body. The General Council stress the need for the utmost effort by the trade unions to extend relief activities among the Spanish people, and they feel that an avoidance of diffusion and overlapping will materially assist. Yours faithfully, Wm Elger Secretary. 292/946/29/29